HUBUNGAN KONSEP DIRI AKADEMIK DENGAN MOTIVASI BERPRESTASI - Winda Permata Sari; Taufik Taufik; Indah Sukmawati (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2016)
Academic self-concept is the views, opinions or feelings about their academic abilities. Achievement motivation is encouragement for individuals to excel. This study is a descriptive correlational study aimed to describe the academic self-concept and achievement motivation of students and to test whether there is a relationship between academic self-concept and echievement motivation of students SMP N 1 VII Koto.subjects numbered 75 students taken high rank in his class. To see the connection techniques used in this study pearson product moment correlationthrough the statistical program SPSS for windows release 17.